(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Respiratory failure remains the most common cause of neonatal morbidity and mortality. Determine the ratio of clinical, subclinical characteristics, causes of respiratory failure. Evaluate treatment outcomes and learn some factors related to neonatal respiratory failure mortality. Methods: escriptive cross-sectional study. There were 157 newborns showing signs of respiratory failure at the Intensive Care Unit Children of Tien Giang Central General Hospital Results: 79.62% of children with respiratory failure were hospitalized on the first day after birth; the male/female ratio was 1.53/1. The most common cause of respiratory failure was neonatal respiratory distress syndrome (42.04%), followed by lung diseases (36.94%), asphyxia (3.28%). The treatment was cured, discharged from the hospital (78.98%), severe enough to die (6.37%), and died (1.91%). The group of children with a gestational age of fewer than 28 weeks has a 7.18 times higher rate of severe disease than children with a gestational age of ³ 37 weeks. The group of children with weight < 1000 grams had a rate of severe disease 6.30 times higher than the group of children with weight ³ 2500 grams. Compared with the group of children with Silverman score ≤ 3 points, the group with Silverman score > 6 points had a 16.00 times higher rate of severe disease. The group of children with mechanical ventilation had a rate of severe disease 6.23 times higher than that of children receiving oxygen; the difference was statistically significant, p < 0.001. Conclusions: Care should be taken in the management of pregnancy, especially in high-risk women. Strengthening neonatal resuscitation skills for district and commune health workers. Early detection and timely treatment of causes of premature birth, fetal malnutrition, fetal distress, perinatal asphyxia.